2012
DOI: 10.1007/s11999-011-2123-4
|View full text |Cite
|
Sign up to set email alerts
|

Pain Relief and Functional Improvement Remain 20 Years After Knee Arthroplasty

Abstract: Background TKA provides demonstrable pain relief and improved health-related quality of life. Yet, a decline in physical function may occur over the long term despite the absence of implant-related problems. Questions/purposes (1) Does pain relief diminish over 20 years after TKA? (2) Does function decline over 20 years in terms of Knee Society function, knee, and walking scores? And (3) Results Pain scores did not diminish over time (average, 49; range, 20-50). Average knee score was 78 (range, 39-97). Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…Although TKAs have provided durable, long-term results [16,18], some patients experience polyethylene wear and osteolysis 5 to 12 years after surgery [3, 6, 11, 13, 24-26, 30, 32]. Collier et al [5] suggested that polyethylene wear is a major risk factor affecting long-term survival of TKA implants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although TKAs have provided durable, long-term results [16,18], some patients experience polyethylene wear and osteolysis 5 to 12 years after surgery [3, 6, 11, 13, 24-26, 30, 32]. Collier et al [5] suggested that polyethylene wear is a major risk factor affecting long-term survival of TKA implants.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions With the numbers available, we found no clinically important differences between HXLPE and lesscrosslinked polyethylene inserts in posterior cruciateEach author certifies that he or she, or a member of his or her immediate family, has no funding or commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article. [16,18,28], some patients experience polyethylene wear and osteolysis 5 to 12 years after surgery [3, 6, 11, 13, 23-26, 30, 32]. Collier et al [5] suggested that polyethylene wear is a major risk factor affecting long-term survival of TKA implants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total joint arthroplasty is a high-volume and high-cost procedure that can reduce pain and restore function in patients with osteoarthritis [8,29,36]. Although most joint arthroplasties can last 15 to 20 years, some fail earlier because of wear and osteolysis, instability, infection, or other causes [1,10,32,34].…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons have traditionally emphasized knee flexion as a hallmark of clinical success [6]. As a result, in the last ten years, manufacturers have introduced novel designs with specific features targeting high flexion.…”
Section: High-flexion Designsmentioning
confidence: 99%